2004
DOI: 10.1051/0004-6361:20034435
|View full text |Cite
|
Sign up to set email alerts
|

The circumstellar environment of the star V923 Aquilae

Abstract: Abstract. V923 Aquilae is a Be shell star that displays emission in Hα, cyclic V/R variations and variations in the intensity of the near infrared continuum. The star presents radial velocity variations arising from a superposition of a long-term cycle and an orbital motion with a period of 214.756 days (Koubský et al. 1989). To investigate the physical properties and the geometry of the circumstellar envelope of this star, we have analysed its spectra in the UV and visual range. We have selected Fe  lines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
3
4
0
2
Order By: Relevance
“…Pavlovski et al (1997) found significant variations in the light curve and color. Arias et al (2004) found variations in the intensity of Fe n lines correlated with the orbital period of 214.75 days, and determined a period of 6.8 years to the V/R variations of the Hey line. The Hey shell line has varied in intensity and V/R ratio from 1999 to the present.…”
Section: The Stellar Samplementioning
confidence: 87%
See 1 more Smart Citation
“…Pavlovski et al (1997) found significant variations in the light curve and color. Arias et al (2004) found variations in the intensity of Fe n lines correlated with the orbital period of 214.75 days, and determined a period of 6.8 years to the V/R variations of the Hey line. The Hey shell line has varied in intensity and V/R ratio from 1999 to the present.…”
Section: The Stellar Samplementioning
confidence: 87%
“…We present in this work new IR spectra of a group of Be stars that were observed simultaneously in both K and L bands. The selected targets are widely studied in the UV and optical range (e.g., Floquet et al 2000Floquet et al , 2002Tubbesing et al 2000;Arias et al 2004;Granada & Cidale 2006;Hirata 1995) and are highly variable objects. We seek to derive the physical conditions of their circumstellar envelopes by a thorough analysis of their H recombination lines.…”
Section: Introductionmentioning
confidence: 99%
“…This star is also a binary system. Arias, et al [20] suggest that the longterm V/R variations correlate with the behavior of the subatomic wind structure. This star is a good candidate to further study its photometric features.…”
Section: Hr7415mentioning
confidence: 99%
“…La intensidad de las líneas de Fe II, correlacionan con el movimiento orbital (Arias et al 2004). Por otro lado, variaciones con un cuasi-período de 7 años fueron encontrados en la banda U con una amplitud de 0.25 mag (Mennickent et al 1994) y de 6.8 años para las variaciones V/R de la línea Hα (Arias et al 2004).…”
Section: Características De Objetos Individualesunclassified